Antegrade intramedullary nailing in proximal humeral fractures: results of 23 cases - Pogliacomi, Francesco; Malagutti, Giovanni; Menozzi, Margherita; Colacicco, Alessandra; Ceccarelli, Francesco; Vaienti, Enrico; Calderazzi, Filippo (Acta Biomedica Atenei Parmensis, 2020)
Introduction: the metaepiphyseal fractures of the proximal humerus represent 5% of all fracturesand mainly affect elderly patients. The type of treatment remain controversial. This retrospective study aimedto evaluate the clinic and radiographic results of 23 patients affected by two or three fragments fractures ofthe proximal humerus with or without metaphyseal extension treated with antegrade intramedullary nailing.Materials and Methods: all patients were clinically evaluated using the “Constant score” (CS) and individualsatisfaction was assessed with a visual scale (VS). Moreover, the fracture’s healing process and the neck shaftangle (NSA) were assessed radiographically. Results: the mean follow-up was 72 months (24-120). Clinicalevaluation and individual satisfaction were positive in most cases (mean CS 79,39 and VS 3,17). Worse resultswere observed in patients over 65 years. Discussion: among the different surgical options intramedullary nailing ensures good fracture stability and high consolidation rate. The entry point through the rotator cuff is ofmain importance as well as proximal nail positioning and choice of the locking screws length. In this studythe functional results of the shoulder are worse in the elderly, who are supposed to have already a degeneratedrotator cuff. Conclusions: antegrade intramedullary nailing should be considered a valid therapeutic option inthis type of fractures. The surgical technique may influence functional results, as consequence of iatrogenicdamage of the rotator cuff.